Potentiometric investigation of the complexation of tungsten(VI) by certain hydroxy-carboxylate ligands - Kruger, Leon (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1988.